Beautiful World Where Are You? - McCarthy, Sinead; Tallant, Sally; Scott, Kitty; Campbell, Nancy; Verwoert, Jan (Liverpool : Liverpool Biennial, 2018)
Aijaz, Madiha ; Akhavan, Abbas ; Allahyari, Morehshin ; Alÿs, Francis ; Arakawa, Ei ; Beasley, Kevin ; Bourouissa, Mohamed ; Cennetoglu, Banu ; Yu-Cheng, Chou ; Ebner, Shannon ; Elliman, Paul ; Eviner, Inci ; Gaisumov, Aslan ; Gander, Ryan ; Grigely, Joseph ; Harding, Dale ; Hendry, Holly ; Joreige, Lamina ; Jungen, Brian ; Kerbel, Janice ; Linklater, Duane ; Lokko, Mae-Ling ; Makhacheva, Taus ; Meyers, Ari Benjamin ; Mohaiemen, Naeem ; Olowska, Paulina ; Osodi, George ; Otto-Knap, Silke ; Poledna, Mathias ; Pootoogook, Annie ; Sattar, Reetu ; Seokyeong Kang, Suki ; Seri, Iacopo ; Smith, Melanie ; The Serving Library ; Varda, Agnès ; Wieland, Joyce ; Yang, Haegue ; Zaman, Rehana
10th Liverpool Biennial, 14 juli tot 28 oktober 2018
boek